GAMBARAN STATUS KETAKUTAN DAN KECEMASAN TERHADAP PERAWATAN GIGI DI WILAYAH ADMINISTRASI KEPULAUAN SERIBU - Lisa Prihastari; ahmad ronal; mega Octaviani (Faculty of Dentistry, Universitas Islam Sultan Agung, 2018)
Background: Most frequent emotional disorders from dental patient are dental fear and anxiety. Previous experiences such as painful tooth extraction, expensive cost, trauma during the last visit to the dentist become factors in the patient’s fear of visiting a dentist. Objective: To determine the description of the fear status and anxiety towards dental care in the Kepulauan Seribu Administration area based on age, sex, income, education, insurance, and dental visits.Method: This study was comparative cross-Sectional analytical research design to determine the relationship between the level of fear and anxiety towards dental care based on sociodemographic factors by giving questionnaires. The tests used were non-parametric and chi-square test.Results: Based on the results of the chi-square test conducted on 116 respondents aged 17-65 years using the MDAS (Modifed Dental Anxiety Scale) test the variables were signifcantly diﬀerence (P <0.05), at group gender and education, while the age variable, income, insurance and visits to the dentist showed no signifcant diﬀerence (P> 0.05). The results from Dental Fear Scale variables that were signifcantly diﬀerence were gender and education variables with values (P<0.05), while variable of age, earning, insurance and visits were not signifcantly diﬀerence (P>0,05).Conclusion: The results can be concluded that gender and education level inﬂuence the dental fear and anxiety in the Kepulauan Seribu region